In Vitro Activity of Statins against Naegleria fowleri - Aitor Rizo-Liendo; Ines Sifaoui; María Reyes-Batlle; Olfa Chiboub; Rubén L. Rodríguez-Expósito; Carlos J. Bethencourt-Estrella; Desirée San Nicolás-Hernández; Edyta B. Hendiger; Atteneri López-Arencibia; Pedro Rocha-Cabrera; José E. Piñero; Jacob Lorenzo-Morales (Pathogens, 2019)
Naegleria fowleri causes a deadly disease called primary amoebic meningoencephalitis (PAM). Even though PAM is still considered a rare disease, the number of reported cases worldwide has been increasing each year. Among the factors to be considered for this, awareness about this disease, and also global warming, as these amoebae thrive in warm water bodies, seem to be the key factors. Until present, no fully effective drugs have been developed to treat PAM, and the current options are amphotericin B and miltefosine, which present side effects such as liver and kidney toxicity. Statins are able to inhibit the 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase, which is a key enzyme for the synthesis of ergosterol of the cell membrane of these amoebae. Therefore, the in vitro activity of a group of statins was tested in this study against two types of strains of Naegleria fowleri. The obtained results showed that fluvastatin was the most effective statin tested in this study and was able to eliminate these amoebae at concentrations of 0.179 ± 0.078 to 1.682 ± 0.775 µM depending on the tested strain of N. fowleri. Therefore, fluvastatin could be a potential novel therapeutic agent against this emerging pathogen.